Varnost v arhitekturi - Kušar, Domen (AR. Arhitektura, raziskave, 2004)
Safety in architecture is a wide concept, which includes many aspects, such as: building mechanics, fire prevention, health and many other fields, whose common goal is ensuring safety for users of buildings. Besides building mechanics and partly also fire safety, which undeniably master their positions, other fields are more or less neglected. The research pointed out numerous hazards that affect architecture and its mission. In the past people developed various safety principles, many of which are today forgotten, although they could still fulfil their functions successfully. It is therefore necessary to point them out and try to find ways of reintroducing them to architectural practise. On the other hand, hazards are also changing. Those, which were formerly the main threat to architecture and its mission have probably lost their significance or have been mastered by the profession. Other hazards have nevertheless become more important and are challenges for present and future practice.
Keywords: architecture; arhitektura; projektiranje; security; varnost; raziskave